Polycarbonyl hexaazatriphenylene derivative type COF for positive electrode material of aqueous zinc ion battery and preparation method thereof

By using polycarbonyl hexazabenzophenylade derivative COF material as the positive electrode material of aqueous zinc ion battery, the existing materials have been solved, and the effects of high capacity, high stability and excellent air self-charging capabilities have been achieved, which is suitable for wearable electronic devices.

CN116425974BActive Publication Date: 2025-03-18CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310171550.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2025-03-18
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

The existing positive electrode materials of zinc ion batteries in water system have problems such as poor conductivity, low energy storage capacity, low air charging capacity and low stability, and it is difficult to meet the needs of high capacity, high stability and excellent air self-charging capacity.

Method used

A polycarbonyl hexazabenzophenylade derivative COF material was used as the positive electrode material, and prepared by dehydration and condensation reaction of hexazabenzophenylade hexacarboxylic trianhydride with dihydrazine terephthalate or N,N-1,4-phenylene bis(thiourea) to form a COF material with a two-dimensional polymerized covalent framework network structure.

Benefits of technology

This COF material significantly improves the rate performance, energy storage capacity and long cycle stability of zinc ion batteries, and has high energy density, power density and excellent bending and folding characteristics, and is suitable for wearable electronic devices. At the same time, COF material exhibits faster self-charge time, flexible switchable self-charge mode, high self-charge capacity and good self-charge cycle stability in air self-charge test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention belongs to the field of synthesis of electrode materials, and particularly relates to a type of polycarbonyl hexaazatriphenylene derivative type COF and a preparation method thereof for aqueous zinc ion battery positive electrode materials. Hexaazatriphenylene hexacarboxylic acid trianhydride is subjected to a dehydration condensation reaction with terephthalic acid dihydrazine or N, N-1,4-phenylene bis (thiourea), and after the reaction is completed, heating is stopped, deionized water, ethanol, and acetone are added for washing, and suction filtration is performed to obtain a polycarbonyl hexaazatriphenylene derivative type covalent organic framework (COF), which is used to prepare aqueous zinc ion battery positive electrode materials, and has high specific capacity, excellent cycle stability, and excellent chemical (air) self-charging performance, therefore, in aqueous zinc ion battery electrode materials and flexible electronic products, it has broad application prospects. The synthesis method of the material of the present invention is simple, the source of raw materials is abundant, and the reproducibility is good, which is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of synthesis of electrode materials, and particularly relates to a polycarbonyl hexaazatriphenylene derivative type COF for positive electrode materials of aqueous zinc ion batteries and a preparation method thereof. Background Art

[0002] With the continuous development of science and technology, people's demand for fossil energy consumption continues to increase. The waste generated by it has brought great pressure on the environment. Exploring renewable energy and new energy storage technologies has become a current research hotspot.

[0003] Since the zinc anode has a high specific capacity (820 mAh g -1 and 5855mAh cm -3 Rechargeable aqueous zinc-ion batteries (AZIBs) have attracted great attention due to their inherent advantages such as low redox potential (-0.76 V relative to standard hydrogen electrode (SHE)), remarkable stability in water, and low cost. In recent years, the development of AZIBs has mainly focused on the design of cathode materials, optimization of electrolytes, and modification of Zn anodes. Among them, the design of cathode materials plays a vital role in improving the electrochemical performance of AZIBs.

[0004] At present, various AZIBs cathode materials have been developed, such as transition metal oxides or sulfides, vanadium-based sodium sulfur compounds and organic compounds. Compared with non-electrode cathode materials, organic cathode materials are renewable, have soft lattice channels that are easy for ion diffusion, and have molecular adjustability. Organic cathode materials also have green and environmentally friendly characteristics. Among them, the covalent organic framework material effectively reduces the dissolution problem of discharge products in small molecule materials by virtue of its polymerized topological network structure. In addition, the high specific surface area, hierarchical porous structure, high thermal stability and chemical stability given by its structure make it attract much attention in energy storage applications (Chem. Sci. 2019, 10, 8889-8894; ACS. Energy. Lett. 2020, 5, 2256-2264). However, since the covalent organic framework material is a network structure constructed by strong covalent bonds, it generally has the characteristics of poor conductivity.

[0005] On the other hand, AZIBs have broad application prospects in the field of wearable electronics. However, in some cases where an external power source cannot be provided, the charging of AZIBs will be limited. To overcome this limitation, many self-charging power systems have been invented and created to extract energy from renewable resources such as sunlight, wind power and air. However, sunlight and wind power are affected by the natural environment and cannot be obtained anytime and anywhere. In contrast, O2 can be obtained for free through the air anytime and anywhere, which should be attributed to the fact that the chemical energy in oxygen molecules can be converted into electrical energy through redox reactions. In recent years, AZIBs with air charging capabilities have received attention (Nat. Commun. 2020, 11, 2199.), but some of them also face the problems of low capacity, low air charging capacity and low stability. Therefore, it is still a challenge to develop new AZIBs with high capacity, high stability and excellent air replenishment capacity. To achieve this goal, it is crucial to synthesize cathode materials with high capacity, high stability and excellent air self-charging ability. Summary of the invention

[0006] In order to further improve the electrochemical energy storage performance of the energy storage system, environmentally friendly and reasonably priced organic positive electrode materials that can be applied in practical fields are continuously developed and expanded. The present invention provides a type of polycarbonyl hexaazatriphenylene derivative type COF for aqueous zinc ion battery positive electrode materials and a preparation method thereof. The structural formula of the COF material is:

[0007] The present invention also provides a method for synthesizing the above-mentioned hexaazatriphenylene derivative: hexaazatriphenylene hexacarboxylic acid trianhydride is subjected to a dehydration condensation reaction with terephthalic acid dihydrazine or N,N-1,4-phenylene bis(thiourea) to prepare a multi-carbonyl hexaazatriphenylene derivative type COF material.

[0008] Specifically, under the protection of inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride, terephthalic acid dihydrazine or N, N-1, 4-phenylene bis (thiourea) and an organic solvent are added to the reactor, and after being fully dissolved and evenly dispersed, the reaction mixture is continuously stirred, the temperature is raised to reflux, and a dehydration condensation reaction is performed. After the dehydration condensation reaction is completed, the heating is stopped, and the mixture is cooled to room temperature and filtered, and finally washed with deionized water and acetone 2-3 times in succession, and vacuum dried to obtain the product, namely HTTH-COF / HTPT-COF, wherein HTTH-COF is a polycarbonyl hexaazatriphenylene derivative type COF material generated by the reaction of hexaazatriphenylene hexacarboxylic acid trianhydride (HHCT) and terephthalic acid dihydrazine (TH), and HTPT-COF is a polycarbonyl hexaazatriphenylene derivative type COF material generated by the reaction of hexaazatriphenylene hexacarboxylic acid trianhydride and N, N-1, 4-phenylene bis (thiourea) (PBT).

[0009] The synthesis reaction equation involved in the present invention is as follows:

[0010]

[0011] Wherein, the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to terephthalic acid dihydrazine is 1:1.5-1:3;

[0012] Alternatively, the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to N,N-1,4-phenylenebis(thiourea) is 1:1.5-1:3.

[0013] The solvent is N,N-dimethylformamide or N,N-dimethylacetamide.

[0014] The inert gas is one of nitrogen or argon.

[0015] The dehydration condensation reaction time is 12-72 hours.

[0016] After the dehydration condensation reaction is completed, the heating is stopped, the mixture is cooled to room temperature and then filtered, washed with deionized water, ethanol and acetone for 2-3 times in sequence, and vacuum dried to obtain the polycarbonyl hexaazatriphenylene derivative type COF material.

[0017] The method for synthesizing the polycarbonyl hexaazatriphenylene derivative type COF material of the present invention is simple, the raw materials are easy to obtain, and the yield is high. At the same time, the method has simple process, low cost and good reproducibility.

[0018] The above-mentioned polycarbonyl hexaazatriphenylene derivative type COF material is used as a positive electrode material for aqueous zinc ion batteries.

[0019] Compared with the prior art, the present invention has the following characteristics:

[0020] The polycarbonyl hexaazatriphenylene derivative COF material of the present invention adopts a heating reflux method, which is relatively simple to operate and has good repeatability. The Zn / / HTTH-COF and Zn / / HTPT-COF battery systems assembled with the derivative COF electrode materials show excellent rate performance and good energy storage capacity in electrochemical tests. In addition, the two-dimensional polymerized covalent framework network structure of the derivative COF material effectively solves the dissolution problem of discharge products in the electrolyte, greatly improving the long cycle stability of the Zn / / HTTH-COF and Zn / / HTPT-COF battery systems. And the flexible Zn / / HTTH-COF and Zn / / HTPT-COF batteries have high energy density, power density and excellent bending and folding characteristics, showing great potential in the application field of wearable electronic devices. Finally, the Zn / / HTTH-COF and Zn / / HTPT-COF flexible batteries showed faster self-charging time, flexible self-charging modes, higher self-charging capacity and better self-charging cycle stability in the air self-charging test. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the infrared spectrum of the polycarbonyl hexaazatriphenylene derivative type HTTH-COF;

[0022] Figure 2 It is the solid state nuclear magnetic resonance H spectrum of polycarbonyl hexaazatriphenylene derivative type HTTH-COF;

[0023] Figure 3 It is the solid state nuclear magnetic resonance C spectrum of polycarbonyl hexaazatriphenylene derivative type HTTH-COF;

[0024] Figure 4 Cyclic voltammograms of polycarbonyl hexaazatriphenylene derivative HTTH-COF button cell at different scan rates;

[0025] Figure 5 This is the rate stability diagram of the polycarbonyl hexaazatriphenylene derivative type HTTH-COF button cell;

[0026] Figure 6 The charge and discharge curves of the polycarbonyl hexaazatriphenylene derivative HTTH-COF button cell at different current densities;

[0027] Figure 7 This is the cycle stability diagram of the polycarbonyl hexaazatriphenylene derivative type HTTH-COF button battery;

[0028] Figure 8 This is the solubility diagram of HTTH-COF of polycarbonyl hexaazatriphenylene derivative type;

[0029] Fig. 9 The energy density and power density diagram of the polycarbonyl hexaazatriphenylene derivative HTTH-COF button cell;

[0030] Fig.10 This is the assembly diagram of the polycarbonyl hexaazatriphenylene derivative type HTTH-COF flexible battery;

[0031] Fig.11 This is the rate stability diagram of the polycarbonyl hexaazatriphenylene derivative type HTTH-COF flexible battery;

[0032] Fig.12 The charge and discharge curves of the polycarbonyl hexaazatriphenylene derivative HTTH-COF flexible battery at different current densities;

[0033] Fig.13 This is the cycling stability diagram of the polycarbonyl hexaazatriphenylene derivative type HTTH-COF flexible battery;

[0034] Fig.14 This is the cycle stability diagram of the polycarbonyl hexaazatriphenylene derivative HTTH-COF flexible battery at different folding angles;

[0035] Fig.15 The charge and discharge curves of the polycarbonyl hexaazatriphenylene derivative HTTH-COF flexible battery at different folding angles;

[0036] Fig.16 The energy density and power density diagram of the polycarbonyl hexaazatriphenylene derivative HTTH-COF flexible battery;

[0037] Fig.17 This is a comparison chart of the self-charging of the polycarbonyl hexaazatriphenylene derivative HTTH-COF flexible battery under argon and air exposure environments;

[0038] Fig.18 This is a diagram showing the free switching of the polycarbonyl hexaazatriphenylene derivative-based HTTH-COF flexible battery under constant current charge and discharge / air self-charging modes;

[0039] Fig.19 This is a graph showing the discharge capacity of the polycarbonyl hexaazatriphenylene derivative-type HTTH-COF flexible battery at different shelf times in an air environment;

[0040] Fig. 20 This is the cycle stability performance diagram of the polycarbonyl hexaazatriphenylene derivative type HTTH-COF flexible battery in the air self-charging-constant current discharge mode;

[0041] Fig.21The capacity-voltage diagram of the polycarbonyl hexaazatriphenylene derivative HTTH-COF flexible battery under air self-charging at different current densities;

[0042] Fig. 22 It is the infrared spectrum of the polycarbonyl hexaazatriphenylene derivative type HTPT-COF;

[0043] Fig.23 This is the liquid NMR H spectrum of the polycarbonyl hexaazatriphenylene derivative type HTPT-COF;

[0044] Fig.24 It is the solid state nuclear magnetic resonance C spectrum of polycarbonyl hexaazatriphenylene derivative type HTPT-COF;

[0045] Fig.25 Cyclic voltammograms of polycarbonyl hexaazatriphenylene derivative HTPT-COF button cell at different scan rates;

[0046] Fig.26 This is the rate stability diagram of the polycarbonyl hexaazatriphenylene derivative type HTPT-COF button cell;

[0047] Fig. 27 The charge and discharge curves of the polycarbonyl hexaazatriphenylene derivative HTPT-COF button cell at different current densities;

[0048] Fig.28 This is the cycle stability diagram of the polycarbonyl hexaazatriphenylene derivative type HTPT-COF button battery;

[0049] Fig.29 This is the solubility diagram of HTPT-COF of polycarbonyl hexaazatriphenylene derivative type;

[0050] Fig.30 The energy density and power density diagram of the polycarbonyl hexaazatriphenylene derivative HTPT-COF button cell;

[0051] Fig.31 This is the assembly diagram of the polycarbonyl hexaazatriphenylene derivative type HTPT-COF flexible battery;

[0052] Fig.32 This is the rate stability diagram of the polycarbonyl hexaazatriphenylene derivative type HTPT-COF flexible battery;

[0053] Fig.33 The charge and discharge curves of the polycarbonyl hexaazatriphenylene derivative HTPT-COF flexible battery at different current densities;

[0054] Fig.34This is the cycling stability diagram of the polycarbonyl hexaazatriphenylene derivative HTPT-COF flexible battery;

[0055] Fig.35 This is the cycle stability diagram of the polycarbonyl hexaazatriphenylene derivative HTPT-COF flexible battery at different folding angles;

[0056] Fig.36 The charge and discharge curves of the polycarbonyl hexaazatriphenylene derivative HTPT-COF flexible battery at different folding angles;

[0057] Fig.37 The energy density and power density diagram of the polycarbonyl hexaazatriphenylene derivative HTPT-COF flexible battery;

[0058] Fig.38 This is a diagram showing the free switching of the polycarbonyl hexaazatriphenylene derivative-based HTPT-COF flexible battery in constant current charge and discharge / air self-charging mode;

[0059] Fig.39 This is a graph showing the discharge capacity of the polycarbonyl hexaazatriphenylene derivative HTPT-COF flexible battery at different shelf times in an air environment;

[0060] Fig.40 This is the cycle stability performance diagram of the polycarbonyl hexaazatriphenylene derivative type HTPT-COF flexible battery in the air self-charging-constant current discharge mode;

[0061] Fig.41 This is the capacity-voltage diagram of the polycarbonyl hexaazatriphenylene derivative HTPT-COF flexible battery under air self-charging at different current densities. DETAILED DESCRIPTION

[0062] The present invention will be further described below by means of specific examples.

[0063] Example 1

[0064] 100 mL of N,N-dimethylformamide (DMF) was added to a 250 mL three-necked flask, and hexaazatriphenylene hexacarboxylic acid trianhydride (purchased from Anaiji) (1.5 mmol 0.6663 g) and terephthalic acid dihydrazine (2.25 mmol 0.4369 g) were added at the same time. After fully dissolved and dispersed, the reaction mixture was continuously stirred at reflux under nitrogen protection. The reaction time was 48 hours. After the reaction was completed, the heating was stopped, and then washed with deionized water and acetone three times in succession. The solid was collected by suction and dried in vacuo at 120°C for 8 hours to obtain a polycarbonyl hexaazatriphenylene derivative type COF material HTTH-COF with a yield of 35%.

[0065] Figure 1 is the infrared spectrum of HTTH-COF, Figure 2 is the solid-state H NMR spectrum of HTTH-COF. Figure 3 This is the solid NMR carbon spectrum of HTTH-COF. The active substance of HTTH-COF, which is used as the electrode material, is mixed with Ketjen black and a binder in a certain proportion. HTTH-COF: Ketjen black: binder (PVDF) = 30%: 60%: 10% (mass ratio) exhibits the best electrochemical performance. After the three are mixed and carefully ground for 2 hours, an appropriate amount of 1-methyl-2-pyrrolidone (NMP) is added and ground again for 0.5 hours, and then it is evenly coated on a titanium mesh or a stainless steel mesh, and vacuum dried at 80°C overnight to form an electrode sheet. The electrode sheet is used as the positive electrode, the zinc sheet is used as the negative electrode, Celgard 2400 (Shanghai Bangtian Industrial Co., Ltd., the same below) is used as the diaphragm, and 2molL -1 ZnSO4 was dissolved in distilled water to make an electrolyte, which was assembled into button cells and flexible batteries, and their electrochemical properties were investigated. Figure 4 Cyclic voltammograms of button cells at different scan rates; Figure 5 This is the rate stability diagram of button cells; Figure 6 It is the charge and discharge curve of button battery at different current density; Figure 7 This is the cycle stability diagram of the button battery; Figure 8 This is the solubility test diagram of HTTH-COF; Fig. 9 Energy density and power density diagram for button cells; Fig.10 This is an assembly diagram of a flexible battery; Fig.11 This is the rate stability diagram of the flexible battery; Fig.12 This is the charge and discharge curve of the flexible battery at different current densities; Fig.13 This is the cycling stability diagram of the flexible battery; Fig.14 This is the cycle stability diagram of the flexible battery at different folding angles; Fig.15 This is the charge and discharge curve of the flexible battery at different folding angles; Fig.16 Energy density and power density diagram of flexible batteries; Fig.17 This is a comparison chart of the self-charging of the battery in argon and air exposure environments; Fig.18 This is a diagram of the flexible battery freely switching between constant current charge and discharge / air self-charging modes; Fig.19 This is a graph showing the discharge capacity of the flexible battery under different storage times in an air environment; Fig. 20 This is the cycle stability performance diagram of the flexible battery in the air self-charging-constant current discharge mode; Fig.21 Capacity-voltage diagram of flexible battery self-charging in air at different current densities.

[0066] Example 2

[0067] The experimental method was the same as that in Example 1, except that the raw material terephthalic acid dihydrazine was replaced with N,N-1,4-phenylenebis(thiourea) (2.25 mmol, 0.5092 g) to obtain a polycarbonyl hexaazatriphenylene derivative type COF material HTPT-COF with a yield of 31%. Fig. 22 This is the infrared spectrum of HTPT-COF. Fig.23 This is the hydrogen NMR spectrum of HTPT-COF. Fig.24 This is the solid NMR carbon spectrum of HTPT-COF. HTPT-COF is used as the active substance of the electrode material, mixed with Ketjen black and a binder in a certain proportion. After multiple screenings, it was finally determined that HTPT-COF: Ketjen black: binder (PVDF) = 30%: 60%: 10% exhibited the best electrochemical performance. After the three were mixed and carefully ground for 2 hours, an appropriate amount of NMP was added and ground again for 0.5 hours, and then evenly coated on a titanium mesh or a stainless steel mesh, and vacuum dried at 80°C overnight to form an electrode sheet. The electrode sheet was used as the positive electrode, the zinc sheet as the negative electrode, Celgard 2400 as the diaphragm, and 2 mol L -1 ZnSO4 was dissolved in distilled water to make the electrolyte, which was assembled into button cells and flexible batteries, and their electrochemical properties were investigated. Fig.25 Cyclic voltammograms of button cells at different scan rates; Fig.26 This is the rate stability diagram of button cells; Fig. 27 It is the charge and discharge curve of button battery at different current density; Fig.28 This is the cycle stability diagram of the button battery; Fig.29 This is the solubility test diagram of HTPT-COF; Fig.30 Energy density and power density diagram for button cells; Fig.31 This is an assembly diagram of a flexible battery; Fig.32 This is the rate stability diagram of the flexible battery; Fig.33 This is the charge and discharge curve of the flexible battery at different current densities; Fig.34 This is the cycling stability diagram of the flexible battery; Fig.35 This is the cycle stability diagram of the flexible battery at different folding angles; Fig.36 This is the charge and discharge curve of the flexible battery at different folding angles; Fig.37 Energy density and power density diagram of flexible batteries; Fig.38 This is a diagram of the flexible battery switching freely between constant current charge and discharge / air self-charging mode; Fig.39 This is a graph showing the discharge capacity of the flexible battery under different storage times in an air environment; Fig.40 The cyclic stability performance diagram of the flexible battery in the air self-charging-constant current discharge mode; Fig.41 Capacity-voltage diagram of flexible battery self-charging in air at different current densities.

Claims

1. A type of polycarbonyl hexaazatriphenylene derivative type COF, characterized in that: The structural formula of the COF is shown below:

2. A method for preparing a polycarbonyl hexaazatriphenylene derivative type COF according to claim 1, characterized in that: The preparation method comprises the following steps: heating hexaazatriphenylene hexacarboxylic acid trianhydride and terephthalic acid dihydrazine or N,N-1,4-phenylenebis(thiourea) to reflux for dehydration condensation reaction, washing, and drying to obtain a multi-carbonyl hexaazatriphenylene derivative type COF.

3. The method for preparing the polycarbonyl hexaazatriphenylene derivative type COF according to claim 2, characterized in that: The dehydration condensation reaction method is: under the protection of inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride and organic solvent, as well as terephthalic acid dihydrazine or N,N-1,4-phenylenebis(thiourea) are added into a reactor, and after being completely dissolved and evenly dispersed, the temperature is raised to reflux under stirring conditions to carry out the dehydration condensation reaction.

4. The method for preparing the polycarbonyl hexaazatriphenylene derivative type COF according to claim 2, characterized in that: After the dehydration condensation reaction is completed, the heating is stopped, the mixture is cooled to room temperature and then filtered, washed with deionized water and acetone for 2-3 times in sequence, and vacuum dried to obtain a polycarbonyl hexaazatriphenylene derivative type COF.

5. The method for preparing the polycarbonyl hexaazatriphenylene derivative type COF according to claim 2, characterized in that: The molar ratio of the hexaazatriphenylene hexacarboxylic acid trianhydride to terephthalic acid dihydrazine or N,N-1,4-phenylenebis(thiourea) is 1:1.5-1:

3.

6. The method for preparing the polycarbonyl hexaazatriphenylene derivative type COF according to claim 3, characterized in that: The organic solvent is N,N-dimethylformamide or N,N-dimethylacetamide.

7. The method for preparing a polycarbonyl hexaazatriphenylene derivative type COF according to claim 3, characterized in that: The dehydration condensation reaction time is 16-72 hours.

8. The method for preparing a polycarbonyl hexaazatriphenylene derivative type COF according to claim 3, characterized in that: The inert gas is one of nitrogen or argon.

9. An application of the polycarbonyl hexaazatriphenylene derivative type COF according to claim 1, characterized in that: The COF is used for positive electrode materials of aqueous zinc ion batteries.

Citation Information

Patent Citations

  • Polycarbonyl nitrogen heterocyclic organic compound for organic cathode material of lithium battery and preparation method thereof

    CN108711624A

  • Polyimide containing hexaazabenzophenanthrene structure and preparation method thereof

    CN114196014A